Reconstructing Law Enforcement Against Digital Content Piracy on Streaming Platforms in Indonesia: An Effectiveness Analysis from a Copyright Perspective - Miranti Dwi Pangesti; Aurora Jillena Meilala; Diani Sadiawati (Journal of Law Perspectives Review, 2026)
Digital content piracy on streaming platforms is one of the major challenges in copyright protection in the era of information technology. This phenomenon has grown along with technological advancement and easy internet access, which are exploited by perpetrators to distribute content illegally without the consent of copyright holders. This research aims to analyze the effectiveness of legal enforcement against digital content piracy in Indonesia, based on Law No. 28 of 2014 on Copyright and other related regulations. The research uses a normative juridical method with a statutory approach and case study analysis, including cases such as IndoXXI and pirated film channels on Telegram. The findings reveal that although the legal framework is normatively sufficient, its implementation remains weak due to the lack of criminal enforcement, limited institutional capacity, and low public legal awareness. Based on Lawrence M. Friedman's legal system theory and Soerjono Soekanto's theory of legal effectiveness, it is concluded that the imbalance between legal structure, legal substance, and legal culture is the main cause of ineffective law enforcement against digital piracy. Therefore, regulatory reform, institutional capacity building, and public education campaigns are urgently needed to ensure more effective copyright protection in the digital space.